Ali je književnost pri pouku slovenščine kot tujega jezika lahko zanimiva? - Grosman, Meta (Jezik in slovstvo, 2004)
Teaching literature can be highly productive component of a foreign language course when designed so that it takes into account the nature of literary works, taking into consideration their features and readership conviction, while being aware of the nature of responding to literature as an intercultural activity. With these basic requirements, a concrete placement of literature needs to be adapted to the profile of foreign language learners.
Keywords: pouk književnosti; Slovene; slovenščina; slovenščina kot drugi ali tuji jezik